The Effects of Positioning During Colonoscopy on Efficacy and Post-procedure Comfort - Ergin, Mustafa; Ergin, Gülencan Yumuşak; Kıvrakoğlu, Fatih; İbiş, Mehmet (Turkish Journal of Gastroenterology, 2025)
Background/Aims: There are studies with different results on improving effectiveness and patient comfort by increasing lumen disten tion through positioning during colonoscopy. In our study, we aimed to compare colonoscopy outcomes and post-procedural patient comfort in the left-lateral and right-lateral positions. Materials and Methods: A total of 231 patients who underwent screening colonoscopy were included. Patients were randomized to either the left-lateral or the right-lateral position. Patient age, sex, comorbidities, body mass index (BMI) values, times to reach the cecum, ileum intubation rates, total procedure times, and colonoscopy findings were compared. Pain and discomfort after the procedure were evaluated and compared with the visual analog scale (VAS) scores at 30 minutes, 6 hours, and 24 hours. Results: Colonoscopy was performed in the left-lateral position in 129 patients and in the right-lateral position in 102. The distributions of age, sex, comorbidities, and BMI values were similar in both groups. The time to reach the cecum and the total procedure time were similar in both groups. There were no significant differences in the findings detected by colonoscopy. There was no significant difference in the post-procedural VAS scores. Conclusion: This study failed to show a difference in colonoscopy outcomes and postprocedural discomfort between the left- and right lateral positions. Cite this article as: Ergin M, Yumuşak Ergin G, Kıvrakoğlu F, İbiş M. The effects of positioning during colonoscopy on effıcacy and post-procedure comfort. Turk J Gastroenterol. 2025;36(3):174-182.